Networked Information Environment: Strategies and Options in Ch. Charan Singh University, Meerut, India - Sukula, Shiva Kanaujia (Journal of Information and Knowledge, 2014)
The paper reflects the networked information environment with emphasis on information services in Ch. Charan Singh University, Meerut, India. Network functions as a critical information service platform for any higher education center. Literature reflects need and provision of networked information services that can cater to vast number of users. Electronic library and information systems are becoming an impressive structure of modern academic systems. This paper discusses academic networked environment, going on strategies and options in Ch. Charan Singh University, Meerut. Now Indian universities are making strategy of encouraging innovation and transformation in higher education by using networks and networked information. The paper reflects status of networking in Ch. Charan Singh University, its components and technical details of networking. Reasons why investment in information technology has been made and key underlying factors affecting use of technology are highlighted. Access management, most searched information, current areas to learn about among the users and benefits to Ch. Charan Singh University academic community are presented. Recommendations for change are highlighted. The paper gives an overview of networked information services in Ch. Charan Singh University, Meerut, India and useful to librarians to discern the gradual change towards establishing network in centers for higher learning (universities) and find out the options and strategies to develop more efficient network to cater information services.